Design of Network and Pole for Meeting Lighting, Communication, and Energy Needs from a Single Source in Disasters - Levent Aksoy; İlknur Yardımcı Coşkun (Doğal Afetler ve Çevre Dergisi)
After disasters, survivors face numerous needs beyond immediate material and medical aid. However, in densely populated cities, post-disaster response times are prolonged. Growing urbanization and population increase the impact of disasters and complicate response plans. Therefore, cities should be equipped to meet essential post-disaster needs, such as lighting, communication, and energy, autonomously. Addressing lighting, communication, and energy needs from a single source in disasters requires a multidisciplinary approach that involves energy efficiency and robust infrastructure solutions. The swift and effective management of post-disaster processes depends on the uninterrupted continuation of these services. In this study, following a systematic literature review, a multifunctional pole design was developed using engineering design methods, and the system's capacity and other parameters were evaluated through mathematical modeling. This hybrid pole provides a network structure offering integrated lighting, energy, and communication services during and after disasters. The pole incorporates various energy generation methods, data transmission options, wireless access points, mobile charging stations, sensors, and IoT devices. This design is expected to play a crucial role in meeting the basic needs of disaster survivors both during and after a disaster.